Creativity and Emotional Intelligence in The Structure of Management Competence of School Leaders - Prystai, Olha (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
The purpose of this article is to describe the results of the study of the components of managerial competence of heads of general secondary education institutions in Ukraine in accordance with the profile of managerial competence generated on the basis of empirical data; to confirm the need for the development of creative thinking and emotional intelligence as important personal qualities and competencies of the leader in the field of education; to analyze the formation of creative thinking and emotional intelligence in the heads of general secondary education institutions of the city of Kyiv. The managerial competence of the school leaders determines their level of professionalism and provides an opportunity for effective implementation of all educational reforms, which in modern Ukraine is a necessary and determining component of the education system of the country. Management effectiveness is the ability to choose the most effective management methods for a given time and circumstances. The range of issues that must be addressed by the head in the educational environment is becoming wider every year, so the level of competence should be appropriate. A clear example of this is the situation that has arisen because of Covid-19 and other unexpected influences, which has radically changed the traditional social order in many areas, including education. Education leaders find themselves in a situation of uncertainty and emotional instability due to a lack of information and excessive responsibility for the new challenges of distance, blended online learning. Heads of educational institutions have been forced to restructure the system of student education and personnel management in many countries around the world. Not everyone has coped with this difficult task. Thus, there is a need to disclose and specify the relationship of managerial competencies and determine the level of development of those professional achievements and personal qualities that contribute to effective management. These problems determined the purpose and objectives of the presented study. This article discusses the soft skills of education leaders, namely creativity and emotional intelligence, in the structure of managerial competence of school leaders. The results obtained during the study showed that in the new conditions of social transformations, the managerial competence of the leader in the field of education is changing significantly. The publication presents the authors’ approximate profile of managerial competence. The levels of development of creative thinking and emotional intelligence were determined by experimental research and correlations between the components of these properties were established, as well as the necessity of their development was substantiated.